Love as a phenomenon of European culture: from ecstasy to ascesis - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article deals with the transformation of medieval mass consciousness caused by antithesis of the spirit and the flesh, typical for medieval culture. It is shown that the manifestations of human sexuality are considered in medieval culture especially in the aspect of sin, whereby earthly love is interpreted as a negative pole of the value scale. All that can be attributed to the sphere of eroticism is considered by medieval culture as a terrifying, chaotic, awesomely and dangerous as phenomenon beyond the rational control. The article shows that these trends lead to the formation of austerity paradigm shift in European culture.